Budgetary impact of increasing use of peritoneal dialysis over haemodialysis in Spain - Gemma Barbado; Carla Garí; Asís Ariznavarreta; Neus Vidal-Vilar; Carlos Alvarez (Health Economics Review)
Abstract Background Chronic kidney disease (CKD) represents a significant public health concern, due to its high prevalence and incidence, as well as its substantial socio-economic costs. In Spain, estimates suggest that the direct healthcare costs of CKD will increase by 13.8% from 2022, which is why the cost of kidney replacement treatment (KRT) programs efficiency and sustainability is under constant analysis. Our analysis aimed to estimate the cost associated with peritoneal dialysis (PD) compared to hemodialysis (HD) from the Spanish National Health System (NHS) perspective and to evaluate the budgetary impact of an increase in the use of PD in our healthcare system environment. Methods The number of patients eligible for KRT was calculated based on the total Spanish population and the incidence and prevalence of patients with end-stage renal disease (ESRD). Patients receiving each modality, type of dialysis, and location of dialysis were estimated. The annual costs of each dialysis modality were calculated and included the cost of dialysis sessions and additional costs (including the cost of peritoneal and vascular access, hospitalisation costs due to potential complications of dialysis, cost of health care personnel, and cost of health care transport used by patients). Population data and costs (€, 2024) were obtained from the Spanish databases and a nephrologist validated the assumptions. Budget impact analysis assessed the incremental budget impact between the current scenario and the alternative scenario, where 30% of incident patients on scheduled HD would receive PD. Results We estimated that in Spain, there are 27,281 prevalent dialysis patients (3,141 receiving PD and 24,140 receiving HD/HDF) and 6,052 incident dialysis patients (1,173 receiving PD and 4,879 HD/HDF). The cost of dialysis amount to €1,555,573,771 (€141,361,374 PD and €1,414,212,397 to HD) in the current scenarios and to €1,540,584,011 (€167,593,157 PD and €1,372,990,854 HD) in the alternative scenario, resulting in a saving of €14,989,760 when 30% of the patients scheduled to receive HD would instead receive PD during the first year. Conclusions The increased use of PD in Spain improves the system’s efficiency, generating significant savings in the treatment of ESRD patients from the NHS perspective.